Region-based Active Contour Model based on Markov Random Field to Segment Images with Intensity Non-Uniformity and Noise - Shahvaran, Zahra (Medknow Publications & Media Pvt Ltd, 2012)
This paper represents a new region-based active contour model that can be used to segment images with intensity non-uniformity and high-level noise. The main idea of our proposed method is to use Gaussian distributions with different means and variances with incorporation of intensity non-uniformity model for image segmentation. In order to integrate the spatial information between neighboring pixels in our proposed method, we use Markov Random Field. Our experiments on synthetic images and cerebral magnetic resonance images show the advantages of the proposed method over state-of-art methods, i.e. local Gaussian distribution fitting.